Subacute toxicity studies of melicope ptelefolia aqueous extract (MPAE) on Sprague Dawley male rats - Nur Azmira Aziz. (2017)
Introduction: Melicope ptelefolia or "Tenggek Burung" is a medicinal herb which known to have an antibacterial and anti-inflammation properties which has the potential to treat pain, fever, wound and itches among Malaysian people. However, its toxic effects need to be elucidated. Objective: This study was performed to evaluate the subacute toxicity effect of aqueous extract of Melicope ptelefolia in Sprague Dawley male rats. Methodology: Subacute toxicity study of aqueous leaves extract of Melicope ptelefolia was carried out in male rats aged seven weeks weighing 150-250 g. They were divided into four groups, i.e. rats being fed on distilled water as a control, Melicope ptelefolia aqueous extract dose 100 mg/kg, Melicope ptelefolia 300 mg/kg and Melicope ptelefolia 500 mg/kg respectively. Subacute toxicity study was conducted by oral administration of the extracts at daily basis of these doses for 28 days. Body weight, mortality and morbidity of the rats were observed throughout the experiment. After 28 days, the rats were sacrificed to isolate the liver, kidney and testis histology as well as blood collected by cardiac puncture which to be evaluated as histopathology, biochemical and haematological parameter. Result: Melicope ptelefolia leaves extract at three doses does not show any significant changes and also there is no sign of toxicity notice for the duration of 28 days. Conclusion: Intake of high doses of this extract may exhibit mild organ toxicity but this study show that Melicope ptelefolia does not cause adverse effect of toxicity at those three different doses.